Hubungan Kondisi UKS Sekolah dengan Pelaksanaan Peran Perawat Sekolah - Abd. Gani Baeda; Risqi Wahyu Susanti; Ekawati Wahyu Saputri (JPP JURNAL KESEHATAN POLTEKKES PALEMBANG, 2025)
Background: The school as a place where the teaching and learning process takes place must become a “Health Promoting School”, meaning that the school can improve the health status of its school community. School Health Services (UKS) can improve the health status of students and create a healthy environment. This study aims to determine the relationship between the condition of school UKS and the implementation of the role of school nurses in the implementation of health education, health services, and the development of a healthy school environment (Trias UKS) in elementary school students in Kolaka Regency. Methods: Written in 3-5 sentences, Results: there was no relationship between the condition of the UKS and the role of school nurses with a p value (0.287). This is because even though the condition of the school UKS is in poor condition, school nurses still perform their role well. Obstacles faced by UKS officers include lack of facilities and infrastructure, lack of awareness of students, parents, and teachers about health, and long distances. Conclusion: This study concludes that although UKS officers perform well, challenges especially related to facilities and health awareness need to be addressed. The development of training and improvement of infrastructure are expected to increase the effectiveness of the role of UKS nurses in providing health services in the school environment